Robustness of observation‐based decadal sea level variability in the Indo‐Pacific Ocean. Issue 14 (30th July 2017) - Nidheesh, A. G.; Lengaigne, M.; Vialard, J.; Izumo, T.; Unnikrishnan, A. S.; Meyssignac, B.; Hamlington, B.; de Boyer Montegut, C.
Abstract: We examine the consistency of Indo‐Pacific decadal sea level variability in 10 gridded, observation‐based sea level products for the 1960–2010 period. Decadal sea level variations are robust in the Pacific, with more than 50% of variance explained by decadal modulation of two flavors of El Niño–Southern Oscillation (classical ENSO and Modoki). Amplitude of decadal sea level variability is weaker in the Indian Ocean than in the Pacific. All data sets indicate a transmission of decadal sea level signals from the western Pacific to the northwest Australian coast through the Indonesian throughflow. The southern tropical Indian Ocean sea level variability is associated with decadal modulations of ENSO in reconstructions but not in reanalyses or in situ data set. The Pacific‐independent Indian Ocean decadal sea level variability is not robust but tends to be maximum in the southwestern tropical Indian Ocean. The inconsistency of Indian Ocean decadal variability across the sea level products calls for caution in making definitive conclusions on decadal sea level variability in this basin. Key Points: Pacific Ocean decadal sea level variability is robust and largely driven by decadal modulation of ENSO and Modoki Indian Ocean decadal sea level variability (either related to or independent from the Pacific) is inconsistent across observation‐based sea level products